2022
DOI: 10.1080/21645698.2022.2106111
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin-mediated temperature stress tolerance in plants

Abstract: Global climate changes cause extreme temperatures and a significant reduction in crop production, leading to food insecurity worldwide. Temperature extremes (including both heat and cold stresses) is one of the most limiting factors in plant growth and development and severely affect plant physiology, biochemical, and molecular processes. Biostimulants like melatonin (MET) have a multifunctional role that acts as a “defense molecule” to safeguard plants against the noxious effects of temperature stress. MET tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 138 publications
1
80
0
Order By: Relevance
“…Melatonin ( N -acetyl-5-methoxytryptamine; MLT) is an indole derivative synthesized from tryptophan through a biosynthetic pathway in animals and plants ( Arnao and Hernández-Ruiz, 2017 , 2021 ; Sharif et al, 2018 ; Raza et al, 2022d ). It is a master regulator that influences many physiological processes in plants.…”
Section: Plant Hormones and Their Interactions With Neurotransmitters...mentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin ( N -acetyl-5-methoxytryptamine; MLT) is an indole derivative synthesized from tryptophan through a biosynthetic pathway in animals and plants ( Arnao and Hernández-Ruiz, 2017 , 2021 ; Sharif et al, 2018 ; Raza et al, 2022d ). It is a master regulator that influences many physiological processes in plants.…”
Section: Plant Hormones and Their Interactions With Neurotransmitters...mentioning
confidence: 99%
“…It is a master regulator that influences many physiological processes in plants. Recent evidence suggests that MLT functions in response to multiple stressors, collaborating with other plant hormones to reduce stress-induced adverse effects, boost antioxidant activity, regulate abiotic stress-induced candidate genes/transcription factors, mitigate oxidative stress, and ultimately improve stress tolerance ( Arnao and Hernández-Ruiz, 2021 ; Sun et al, 2021 ; Siddiqui et al, 2022 ; Raza et al, 2022d ). The conferring mechanisms of MLT associated with abiotic stress tolerance that ensures redox homeostasis has been well-studied ( Arnao and Hernández-Ruiz, 2021 ; Siddiqui et al, 2022 ).…”
Section: Plant Hormones and Their Interactions With Neurotransmitters...mentioning
confidence: 99%
“…Climate change and crop production are directly correlated with each other, and current climate changes significantly impact agricultural productivity (Sharma et al, 2021 , 2022 ; Farooq et al, 2022 ). Mainly, different biotic diseases and abiotic environmental factors greatly affect the productivity and overall quality of various crop plants around the world (Irfan et al, 2016 , 2021 ; Kumar et al, 2016 ; Jiang et al, 2017 ; Ansari et al, 2022 ; Raza et al, 2022a , b ). Peanut ( Arachis hypogaea L.) is one of the most important oil crops in the world, but its yield is severely limited by various biotic and abiotic stresses (Mishra et al, 2015 ; Gangurde et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 10 Studies in plants have shown that MEL regulates plant growth, root morphogenesis, floral transformation, and responses to multiple abiotic stresses, 11–17 including cold stress. 14 , 18 For instance, MEL can alleviate the drought stress of wheat, rapeseed and maize by reducing the malondialdehyde (MDA) contents. 19–21 In Limonium bicolor, wheat, and cotton, MEL improved salt tolerance by enhancing the antioxidant enzyme activities and the content of soluble sugar.…”
Section: Introductionmentioning
confidence: 99%
“…25 In conclusion, MEL has been widely used to improve the tolerance against drought, salt, and cold stress. However, in response to cold stress, most studies have been carried out to identify the MEL-induced stress tolerance mechanisms at physiological and biochemical levels in different crop plants; 14 , 18 still, little is known about MEL-induced cold tolerance in rapeseed. Thus, there was a dire need to evaluate the positive impact of MEL in rapeseed seedlings at molecular level.…”
Section: Introductionmentioning
confidence: 99%